THE INFLUENCE OF SOCIAL MEDIA ON INTERACTION PATTERNS AMONG TEENAGERS - Indah Sulistiani; Sulaiman; Magdalena Depriyani; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
Social media has revolutionized interaction patterns among teenagers, providing them with new opportunities to communicate and share experiences like never before. However, an important issue that arises is how intensive use of social media affects mental health and the development of social skills. The tendency to spend excessive time online can reduce opportunities for in-person interactions that are important for social and cognitive learning. The lack of face-to-face contact can hinder adolescents in developing empathy and non-verbal communication skills. Furthermore, constant social comparison and the search for online validation can trigger psychological distress, including self-esteem issues and anxiety. The research method in this study uses literature research method. The results show that social media provides ample opportunities for adolescents to connect socially, explore identity, and participate in online communities. However, adolescents' use of social media also poses significant challenges. In particular, findings suggest a correlation between intensive social media use and an increased risk of mental health problems such as depression and anxiety, as well as a reduction in face-to-face interactions that may affect the development of healthy social and emotional skills.